PW 1007 Sex and gender disparities in epidemiologic features and clinical outcomes of bicyclists injuries. (November 2018) - Lee, Seung Chul; Lee, Sanghun; Lee, Jeong Hun; Kim, Jae Seong; Seo, Jun Seok; Do, Han Ho; Lee, Ji Hoon; Cho, Wonjin
Abstract : Background: Bicycling is an increasingly popular recreation and mode of transportation in korea. Improved understanding of sex and gender-specific differences in epidemiologic features and clinical outcomes in bicycling injuries could help to understand bicycle-related injuries and develop preventative strategies. Aims: This study aimed to investigate sex and gender-specific differences in epidemiologic features and clinical outcomes in bicycling injuries. Methods: This is a cross-sessional study based on the Emergency Department(ED)–based Injury In-depth Surveillance(EDIIS) database from 23 EDs in Korea. All of injured bicyclists between January 1, 2011. and December 31, 2016. were eligible, excluding cases with unknown outcomes. The primary outcome was intracranial injury and the secondary outcomes were in-hospital mortality and clinical important injury (admission or in-hospital death). We calculated adjusted odds ratios (AORs) of gender(male) for study outcomes after adjusting for potential confounders. Results: Among 24 306 eligible patients, 19 286 (79.3%) patients were male and 5 020 (20.7%) were female. The rate of helmets use was no diferrence(10.6% in male and 10.2% in female, respectively). Bicycling injuries of male occurred more in child and adolescent, evening and night(all p<0.05). In the multivariable logistic regression models, male was more likely to have intracranial injury(3.9% vs 3.1%, AOR: 1.22 (1.01–1.46), in-hospital mortality (0.9% vs 0.5%, AOR: 1.71 (1.12–2.60) and clinical important injury (15.6% vs 14.6%, AOR: 1.13 (1.03–1.24). Discussion and conclusions: There were gender-specific differences in epidemiologic features and clinical outcomes in bicycling injuries. Bicycling injuries of male occurred more in child and adolescent and had more severe outcomes than female. Preventative strategies to reduce the bicycling injuries targeting male (esp, child and adolescent male) are needed.